Impact of Vocational Training Programme on Income and Employment Generation for Rural Youth in Dewas District of Madhya Pradesh - Nishith Gupta, Neerja Patel, K.S. Bhargav, Moni Singh and A.K. Dixit (Indian Journal of Extension Education, 2018)
Various efforts for agriculture and rural development have been made by the government to encourage thefarmers to adopt new agricultural technologies and efficient practices to change their situations for economicprosperity and livelihood security. In this regard Krishi Vigyan Kendra, Dewas (MP) conducted vocationaltrainings for rural youths on “Nursery Management of vegetables” and “Vegetative propagation techniques infruit plants” from 2007-2012, 2014 and 2016 with the objective to give rural youths self employment. theresults revealed that majority (53.33%) of respondents had low income, while 26.67 percent and 20.00 percentwere in medium and high income categories, respectively. Higher percentage (50.00%) of the respondentswere of medium income category, while 36.67 per cent and 13.33 per cent were of low and high incomecategories, respectively.